Pengaruh Suhu Pada Proses Degradasi Fenol Dengan Menggunakan Komposit Titania-Carbon Nanotube(Cetyltrimethylammonium Bromide) - Avisa, Utari; Heltina, Desi; Fermi, M Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
One type of hazardous industrial waste is phenol. The photocatalysis process has become the choice for the treatment of phenol waste. Titanium dioxide or titania (TiO2) is a photocatalyst material that is often used. Carbon nanotubes (CNT) are known to be used to improve the performance of TiO2 photocatalyst material. The CNT used was modified with CTAB (Cetyltrimethylammonium bromide) surfactant. The purpose of this research are to determine the effect of temperature degradation on the performance of the Titania-CNT (CTAB) composites in degrading phenols through the process of photocatalysis. The study began with surface modification of CNT using CTAB surfactant. Then the modified CNT was compiled with TiO2. Then Titania-CNT (CTAB) composite performance in degradating phenol was tested using a variation of the degradation temperature of 40oC and 50oC. The results of this research indicate that as the temperature increases, the phenol which can be degraded by the Titania-CNT (CTAB) composite is also increasing. The highest effectiveness of composite TitaniaCNT (CTAB) performance was obtained when the degradation temperature of 50oC was 99.54%. Keywords : phenol, photocatalysis, composites, TiO2, CNT, CTAB